Pectolytic Enzymes in Three Populations of Ditylenchus dipsaci - Chitwood, David J. (Society of Nematologists, 1977)
Extracts of nematodes of the Raleigh, North Carolina (RNC), Waynesville, N. C. (WNC), and onion populations of Ditylenchus dipsaci were examined for pectolytic activity. RNC nematodes contained a NaCl-stimulated endo-polymethylgalacturonase with optimal pH for activity of 6.0, whereas nematodes of the WNC and onion populations possessed a NaCl-stimulated endo-polygalacturonase with pH optimum of 4.0. Nematodes of each population also contained a CaCl₂-activated endo-pectin methyl-trans-eliminase with optimal pH of 9.0. Nematode extracts containing 0.5 M NaCl macerated potato discs. RNC and onion nematodes induced gall formation in Wando pea seedlings, but WNC nematodes induced a resistant, hypersensitive response. Thus pectolytic activity was not correlated with pathogenicity of D. dipsaci on Wando pea.